2017
DOI: 10.3892/mmr.2017.8349
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside inhibits steroid-induced avascular necrosis of the femoral head via the PI3K/Akt signaling pathway: In�vitro and in�vivo studies

Abstract: Dexamethasone (Dex) and other glucocorticoids are widely used to treat serious infections and immunological diseases, however they may cause steroid-induced avascular necrosis of the femoral head (SANFH). Salidroside (Sal) has demonstrated an anti-apoptotic effect on neurocytes by activating the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway. In the present study, primary osteoblasts were used in vitro and in rats in vivo to determine the anti-apoptotic effect of Sal on SANFH. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Nevertheless, only the phosphorylation of PI3K and Akt mainly participate in these physiological activities. Besides, growing numbers of studies have found that cell apoptosis is closely related to the PI3K/Akt pathway ( Xue and Feng, 2018 ; Zhan and Yan, 2020 ). Therefore, we evaluated the effect of BTP on the PI3K/Akt pathway in osteoclasts.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, only the phosphorylation of PI3K and Akt mainly participate in these physiological activities. Besides, growing numbers of studies have found that cell apoptosis is closely related to the PI3K/Akt pathway ( Xue and Feng, 2018 ; Zhan and Yan, 2020 ). Therefore, we evaluated the effect of BTP on the PI3K/Akt pathway in osteoclasts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Dex can induce osteoblast apoptosis and SANFH in rat or human specimens by upregulating caspase-3 ( 20 , 41 ). Bcl-2 is an anti-apoptotic gene, whereas Bax is a pro-apoptotic gene ( 3 ) and studies have reported that the cause of Dex-induced osteoblast apoptosis is the imbalance between Bcl-2 and Bax (mitochondrial dysfunction) ( 42 , 43 ). Additionally, Dex treatment can increase ROS production and excessive ROS may cause cell apoptosis through the mitochondrial-mediated caspase apoptosis pathway ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH) is one of the most common diseases affecting the hip joint, resulting in severe pain or joint disability ( 1 , 2 ). Steroid-induced avascular necrosis of the femoral head (SANFH) is the most common type of ONFH ( 3 ). If patients with SANFH are not treated properly, the femoral head may collapse, resulting in hip function damage and disability ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt pathway is associated with various fundamental cellular processes, including survival, proliferation, growth and differentiation (33). Xue et al (34) reported that Salidroside alleviated the dexamethasone-induced apoptosis of osteoblasts by downregulating caspase-3 and activating the PI3K/Akt signaling pathway in osteoblasts. In addition, the osteogenic differentiation-inducing and bone regenerative properties of graphene-incorporated poly(lactic-co-glycolic acid) were mediated via the activation of the PI3K/Akt/glycogen synthase kinase 3β/β-catenin signaling pathway (35).…”
Section: Discussionmentioning
confidence: 99%